Trends in sensor-based health metrics during and after pregnancy: descriptive data from the apple women's health studyAJOG Global Reports at a Glance - Anshuman Mishra, PhD; Jihyun Park, PhD; Ian Shapiro, PhD; Tyler Fisher-Colbrie, MBA; Donna D. Baird, PhD; Sanaa Suharwardy, MD; Shunan Zhang, PhD; Anne Marie Z. Jukic, PhD; Christine L. Curry, MD, PhD (Elsevier, 2024)
Background: While it is known that vital signs and behaviors change during pregnancy, there is limited data on timing and scale of changes for sensor-derived health metrics across pregnancy and postpartum. Wearable technology provides an opportunity to understand physiologic and behavioral changes across pregnancy with greater detail, more frequent measurements, and improved accuracy. The aim of this study is to describe changes in physiologic and behavioral sensor-based health metrics during pregnancy and postpartum in the Apple Women's Health Study (AWHS) and their relationship to demographic factors. Methods: The Apple Women's Health Study is a digital, longitudinal, observational study that includes U.S. residents with an iPhone and Apple Watch. We evaluated changes from pre-pregnancy through delivery and postpartum for sensor-derived health metrics. Minimum required data samples per day, week and overall were data element specific, and included 12 weeks prior to pregnancy start, and 12 weeks postpartum for pregnancies lasting between 24 and 43 weeks. Findings: A total of 757 pregnancies from 733 participants were included. Resting heart rate (RHR) increased across pregnancy, peaking in the third trimester (pre-pregnancy median RHR 65.0 beats per minute [BPM], interquartile range [IQR] 60.0-70.2 B.M. third trimester median RHR 75.5 B.M. IQR 69.0-82.0 B.M., with a decrease prior to delivery and nadir postpartum (postpartum median RHR 62.0 B.M. IQR 57.0-66.0 B.M.. Heart rate variability (HRV) decreased from pre-pregnancy (39.9 milliseconds, IQR 32.6-48.3 milliseconds), reaching a nadir in the third trimester (29.9 milliseconds, IQR 25.2-36.4 milliseconds), before rebounding in the last weeks of pregnancy. Measures of activity, such as exercise minutes, stand minutes, step count and Cardio Fitness were all decreased in each trimester compared to pre-pregnancy, with their nadirs postpartum. Total sleep duration increased slightly in early pregnancy (pre-pregnancy 7.2 hours, IQR 6.7-7.7 hours; 1st trimester 7.4 hours, IQR 6.8-7.9 hours), with the lowest sleep duration postpartum (6.2 hours, IQR 5.4-6.8 hours). Interpretation: Resting heart rate increased during pregnancy, with a decrease prior to delivery, while heart rate variability decreased across pregnancy, with an upward trend before delivery. Behavioral metrics, such as exercise and sleep, showed decreasing trends during and after pregnancy. These data provide a foundation for understanding normal pregnancy physiology and can facilitate hypothesis generation related to physiology, behavior, pregnancy outcomes and disease.